The Admissibility of Extrinsic Evidence in the Interpretation of Double Tax Conventions - A South African Perspective - Claassen, Theunis Cornelis (Department of Finance and Tax, 2021)
A recent South African judgment concerning the application of the most favoured nation clause in the South Africa/ Netherlands double tax convention has once again raised questions regarding the correct approach to the interpretation of treaties in South Africa and what information should be admissible as part of this process. In particular the court's strict approach to the admissibility of extrinsic evidence in the interpretation of double tax treaties and the application of the parol evidence rule requires further investigation. This dissertation considers this question by first analysing the approach to interpretation and the admission of extrinsic evidence as provided for under the Vienna Convention on the Law of Treaties. Thereafter, the South African domestic approach to interpretation and the principles regulating the admission of extrinsic evidence is considered. A particular focus is placed on the parol evidence rule as applied by South African courts. Following this analysis, the dissertation proceeds with a comparison of the two approaches in order to determine any commonalities and differences that might exist. Through this process of comparison, the dissertation finds that the contemporary South African approach to interpretation, is largely aligned with the approach in the Vienna convention, subject to certain limitations on evidence admissibility as provided for under the domestic parol evidence rule. The dissertation concludes that it would be appropriate for a South African court to apply the ordinary domestic principles of interpretation when interpreting tax treaties, provided that this process must still be informed by the principles of the Vienna Convention, other sources of customary international law and foreign case law on the interpretation of treaties. The interpretive process would nevertheless remain subject to the domestic principles of evidence admissibility and the parol evidence rule.